FATCO syndrome (fibular aplasia, tibial campomelia, and oligosyndactyly ) in newborn in Serbia – A case report - Almir Kajevic; Haris Plojovic; Dzemail Smail Detanac; Suada Malicevic; Azra Kajevic; Dzenana Avdo Detanac; Mirza Corovic (Zdravniški Vestnik)
FATCO syndrome (Fibular aplasia, tibial campomelia, and oligosyndactyly ) is a very rare malformation of an unknown genetic basis. It more commonly occurs in male children, and the lower extremities are more frequently affected. This is a case of a male newborn with the rare FATCO syndrome. It is the first child of healthy, unrelated parents. The pregnancy, being the first, was regular, monitored, and concluded with a cesarean section at 39 weekswithout any complications. The 33-year-old mother denies taking medication during pregnancy but reports having had COVID-19 in the fourth month of pregnancy. The newborn has normal upper extremities and the left lower extremity. The right lower extremity exhibits a shorter, curved lower leg with reduced circumference. A dimple is observed on the skin on the anterior side of the shin. There is a missing fifth toe on the right foot. Treatment involves a multidisciplinary approach and orthopedic-surgical corrections after birth to avoid varying degrees of disability.